Non-parametric wavelet based texture synthesis - KOKARAM, ANIL CHRISTOPHER (My University, 2005)
This paper presents a new algorithm for synthesising image texture. Texture synthesis is an important process in image post-production. Previous approaches can be classified as either parametric or nonparametric. Of these nonparametric approaches have achieved the most impressive results. Unfortunately, these methods generally suffer from high computational cost and difficulty in handling scale in the synthesis process. This paper introduces a new idea of using wavelet decomposition as a basis for nonparametric texture synthesis. The results show an order of magnitude improvement in computational speed and a better approximation of the dominant scale in the synthesised texture.
PUBLISHED
Keywords: Electronic & Electrical Engineering